1976
DOI: 10.1038/bjc.1976.189
|View full text |Cite
|
Sign up to set email alerts
|

The effect of isoprenaline on induction of tumours by methyl nitrosourea in the salivary and mammary glands of female wistar rats

Abstract: Summary.-Pretreatment of rats with isoprenaline sulphate (IPR) stimulated DNA synthesis in both salivary and mammary gland tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1978
1978
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 25 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…Since similar nodular proliferation was not observed in the controls, the proliferation may be eonsidered the result of the combined effeet of isoproterenol and X-irradiation. Enhancement of the neoplastic effeet of several agents ineluding X-irradiation by stimulating the target cells to proliferate has been reported by Cole & Nowell (1965) and by Parkin & Neale (1976).…”
Section: B Reparative and Proliferative Changesmentioning
confidence: 91%
“…Since similar nodular proliferation was not observed in the controls, the proliferation may be eonsidered the result of the combined effeet of isoproterenol and X-irradiation. Enhancement of the neoplastic effeet of several agents ineluding X-irradiation by stimulating the target cells to proliferate has been reported by Cole & Nowell (1965) and by Parkin & Neale (1976).…”
Section: B Reparative and Proliferative Changesmentioning
confidence: 91%
“…In fact, several studies have shown that adrenergic stimulation may suppress synthesis and secretion of milk proteins, as described for stress exposure (Bisset et al, 1967; “Catecholamine antagonism to oxytocin‐induced milk‐ejection,” 1971; Chiba et al, 2019; Clapp et al, 1985; S. L. Song et al, 1988). Furthermore, in models of chemically induced breast cancer, it was shown that exposure to stress or to adrenergic agonists can accelerate the onset of cancer (Adamekova et al, 2003; Boyd et al, 2010; Parkin & Neale, 1976), whereas propranolol, a nonselective β‐adrenoceptor antagonist, can delay its appearance (Tibensky et al, 2021). The results from epidemiological studies may also be taken as an indicator for such connection between stress/adrenergic stimulation and cancer incidence since a correlation between stress exposure and breast cancer incidence has been reported (Chiriac et al, 2018; Kruk et al, 2019; P. Li et al, 2016; Lillberg et al, 2003).…”
Section: The Adrenergic System In the Breast Tumor Microenvironmentmentioning
confidence: 99%
“…Thyroid tumor incidences were maxi mal when X-ray treatments were timed at the peak of cell proliferation and remained high throughout an extended period of elevated thyroid cell proliferation. Parkin and Neale [14] evaluated carcinogenesis in salivary glands of rats treated with isoprenaline sul fate. Isoprenaline sulfate pretreatments pro duced a marked (12-fold) stimulation of cell proliferation in the salivary glands but only a 2-to 3-fold increase in mammary gland cell proliferation.…”
Section: Studies In Tissue Cells In Vivomentioning
confidence: 99%